Brain surface morphology and ecological and macroevolutionary inferences of avian New World suboscines (Aves, Passeriformes, Tyrannides) - Demmel Ferreira, María Manuela; Degrange, Federico Javier; Tirao, Germán Alfredo (2024)
Fil: Demmel Ferreira, María Manuela. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales. Centro de Investigaciones en Ciencias de la Tierra; Argentina.